Jumbo squid in the eastern Pacific Ocean: A quarter century of challenges and change - Rodhouse P.G.K. (2016)
We warmly thank the Contralmirante Germán Vásquez-Solis, President of the Instituto del Mar del Perú (IMARPE) for support and encouragement for us to organize the 6th International Symposium on Pacific Squids and the 5th International Workshop that were held in Lima and Callao, Perú, and the directors, scientists and administrators of IMARPE for their scientific and logistic support during the symposium. Special thanks to the Cephalopod International Advisory Council (CIAC), Ministerio de la Producción (PRODUCE), Consejo Nacional de Ciencia y Tecnología (CONCYTEC), Instituto Tecnológico de la Producción (ITP), the Korean Institute of Ocean Science and Technology (KIOST), Institute de Recherche pour le Développement (IRD) and Ministerio de Comercio Exterior y Turismo (MINCETUR) for their scientific and logistic support.